Gynecological problems and reproductive health awareness amongst late adolescent girls pursuing professional courses: a questionnaire based survey - Chennuru, Rambabu; Srungavarapu, Revathi; Ikkurthy, Niharika Sarma; Begum, Jarina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Dysmenorrhoeais a debilitating menstrual problem and may be related to body mass index (BMI). This study was done to explore the various gynecological problems in girls in their late adolescence that is pursuing professional courses in medicine, dental and nursing. Methods: This was a prospective, questionnaire based study conducted between January and February 2019 in a medical college in Visakhapatnam, India. The survey included female undergraduate students of the Medical, Dental and Nursing colleges to find out their menstrual history and reproductive awareness with the help of a self-structured questionnaire. Participants were categorized based on BMI. Data was reported as number and percentage. Results: Of the 190 participants, 154 participants (age range; 16-19 years) were included in the study. Fifty percent of the total participants reported to have dysmenorrhoea, of which 21% reported severe dysmenorrhoea. A very high % of participants in the obese category (77.8%) reported severe dysmenorrhoea, followed by 27.3% in the underweight category. A U-shaped relationship between percentage of participants with severe dysmenorrhoea and increasing BMI was observed. A fair percentage of obese participants reported for infrequent periods beyond 35-45 days and androgenic features like excess hair, acne and dark pigmentation around neck, suggestive of polycystic ovarian syndrome (PCOS). The participants possessed a high level of awareness and reported in the range of 87.1 to 96.8% related to reproductive health. Conclusions: Despite high level of awareness among the participants we observed a considerably high prevalence of dysmenorrhoea which was even more prevalent, in the obese category.